The Role of Plant Additives in Enhancing the Productive and Immune Performance of Ruminants: Article Review - Abdullah, Sara hatem (American Journal of Botany and Bioengineering, 2025)
known as saponin humid acids), and tannins—have taken their place in ruminant nutrition as natural alternatives to antibiotic growth promoters. This narrative review of literature from 2021 to 2025 surveys their effects on productive yields, the immune system, and environmental sustainability. Between 34 beef experiments and studies of 23 dairy operations, EOP or sapogenin products raised average daily gains by 4–8%, and energy-corrected milk yield by 3–5%. They also reduced the conversion factor for feed roughly "A good approach for the future would be to phase in large-scale safety multi-generation trials. Meta-analysis and controlled experiments have all reported that additional success in all these areas includes reinforced humoral immunity: higher IgG, IgM titres, and neutrophil activity; reduced oxidation stress marker quantities (↓ MDA; ↑ GPx, CAT). Environmental assessments show that enteric methane emissions could be reduced by about 5–15%, with lower urinary nitrogen excretion, and 21% less dung patch N₂O. Economically viable, documented return on investment can be over 10 times costs, and emerging carbon credit schemes could offset the entire cost of addition. Adoption strategy needs to focus on the selection of EFSA/FDA-registered products, making full use of micro-encapsulated forms for addition to pellet feeds, and adjusting the level of dose against milk urea nitrogen or rumen NH₃ N to avoid protein binding excessively. A good approach for the future would be to phase in large-scale safety multi-generation trials to confirm both duration of effectiveness and ADR profile, meta-omics over time to elucidate mode of action in detail, AI-directed dosage optimization with multi-strand mixtures, and trials involving cattle across various races and different climatic zones of a coordinated field study program. Collectively, PFA provides a way of work for ruminant systems that are more productive, resilient, with a much smaller footprint in terms of carbon.